2016
DOI: 10.1039/c6ew00207b
|View full text |Cite
|
Sign up to set email alerts
|

Fate of microplastics and other small anthropogenic litter (SAL) in wastewater treatment plants depends on unit processes employed

Abstract: The accumulation of microplastics (plastic particles less than 5 mm) and similarly sized small anthropogenic litter (SAL; e.g., cellulosic products manufactured from natural material) in aquatic ecosystems is a growing concern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
180
0
12

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 228 publications
(217 citation statements)
references
References 27 publications
11
180
0
12
Order By: Relevance
“…Microplastic morphological characteristics (shape, texture, and size) may influence toxicological outcomes, for example, controlling if it is translocated in the tissues, blocks the digestive tract, or irritates or lacerates tissues, resulting in abnormalities or increasing susceptibility to infectious diseases. Growing research suggests that microfibers are a prevalent form of plastic pollution in the environment (Güven et al, ; Panno et al, ; Michielssen et al, ). Their dimensions may present novel risks, as they are more likely to penetrate or otherwise irritate tissues.…”
Section: Microplastic Uptake and Consequences In Biotamentioning
confidence: 99%
“…Microplastic morphological characteristics (shape, texture, and size) may influence toxicological outcomes, for example, controlling if it is translocated in the tissues, blocks the digestive tract, or irritates or lacerates tissues, resulting in abnormalities or increasing susceptibility to infectious diseases. Growing research suggests that microfibers are a prevalent form of plastic pollution in the environment (Güven et al, ; Panno et al, ; Michielssen et al, ). Their dimensions may present novel risks, as they are more likely to penetrate or otherwise irritate tissues.…”
Section: Microplastic Uptake and Consequences In Biotamentioning
confidence: 99%
“…An analysis of 29 Great Lakes tributaries (Baldwin et al, 2016) found total debris comprised of 71% fibers and 17% fragments. Similarly, anthropogenic litter in the effluent of a high capacity wastewater treatment plant that discharges directly to the Great Lakes was found to be 61% fibers and 33% fragments (Michielssen et al, 2016). This difference may be due to the fact that typically fibers are comprised of polymers that are denser than water, e.g., nylon, polyester, acrylic.…”
Section: Secondary Plastics (Fragments) Were the Most Common Plastic mentioning
confidence: 99%
“…Field surveys have confirmed the presence of microplastics in Great Lakes surface water (Eriksen et al, 2013;Mason et al, 2016), sediment (Corcoran et al, 2015;Ballent et al, 2016), and beaches (Zbyszewski and Corcoran, 2011;Hoellein et al, 2014;Zbyszewski et al, 2014;Driedger et al, 2015), as well as the rivers (Baldwin et al, 2016) and wastewater treatment plant (WWTP) effluents (Michielssen et al, 2016) that directly feed into the Great Lakes. Yet, these data are sparse.…”
Section: Introductionmentioning
confidence: 99%
“…Among them can be distinguished: wastewater treatment plants, cargo shipping, fisheries, human waste from beaches and urban runoff [Cole et al 2011, Stolte et al 2015, Peters and Bratton 2016, Alomar et al 2016, Michielssen et al 2016, Solomon and Palanisami 2016, Graca et al 2017, Mintening et al 2017, Wright and Kelly, 2017 Baltic Sea water, which suggests that tourist activity could be a major entry path for potential synthetic fibres as well.…”
Section: Sources and Transport Pathsmentioning
confidence: 99%